Design and Validation of an Educational Model for Allameh Tabataba'i University in the Context of the COVID-19 and Post-COVID-19 Era - Nili Ahmadabadi, Mohammad Reza; Ghorbani, Maryam; Zaraii Zavaraki, Esmaeil; Abbaspour, Abbas; Asgari, Mohammad (Assessment and Practice in Educational Sciences, 2026)
The present study aimed to design and validate an educational model for Allameh Tabataba'i University under the conditions of the COVID-19 and post-COVID-19 periods. The research employed a mixed-methods design. Using thematic analysis and grounded theory approaches, the study proposed two distinct educational models. The research population included full-time and adjunct faculty members, PhD students, and top-ranking students from the faculties of Allameh Tabataba'i University. The sample was selected through purposive sampling, and following the principle of theoretical saturation, a total of 13 interviews were conducted. The proposed models were validated using the fuzzy Delphi technique, and confirmation of the models was obtained from 10 subject-matter experts. The first model, based on the ADDIE instructional design framework, included five components: educational infrastructure and support, instructional and content design, evaluation and learning assessment, educational roles and interactions, and emerging technologies with artificial intelligence. The second model presented a sub-theory within the framework of grounded theory. In this model, the design of an effective educational model was identified as the central phenomenon influenced by causal conditions such as change-inducing factors, contextual conditions such as technological infrastructure, and intervening conditions such as university policy. Ultimately, strategies such as the development of infrastructure and flexible instructional design were proposed, leading to learner-centeredness and crisis preparedness as the resulting outcomes.